2019
DOI: 10.1002/hed.25861
|View full text |Cite
|
Sign up to set email alerts
|

Home enteral nutrition may prevent myelosuppression of patients with nasopharyngeal carcinoma treated by concurrent chemoradiotherapy

Abstract: Background The aim of this study is to assess the effect of home enteral nutrition (HEN) on the myelosuppression of patients with nasopharyngeal cancer (NPC) during the course of concurrent chemoradiotherapy (CCRT). Methods A total of 18 outpatients with NPC administered oral nutritional supplementation intervention at home during the course of CCRT were designated as the HEN group, whereas 36 patients with NPC who had previously completed CCRT were retrospectively included as the control group. Patient Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(88 reference statements)
2
7
0
Order By: Relevance
“…In post-discharge colorectal cancer surgery patients who were in ONS intervention group showed reduced skeletal muscle loss compared to those in the control group, however, no difference was found in other biochemical markers (Tan et al, 2021). Similar results were observed when the patients were treated with home enteral nutrition (Li et al, 2019). In this study, we also found no significant difference in nutritional status markers between two groups.…”
Section: Discussionsupporting
confidence: 81%
“…In post-discharge colorectal cancer surgery patients who were in ONS intervention group showed reduced skeletal muscle loss compared to those in the control group, however, no difference was found in other biochemical markers (Tan et al, 2021). Similar results were observed when the patients were treated with home enteral nutrition (Li et al, 2019). In this study, we also found no significant difference in nutritional status markers between two groups.…”
Section: Discussionsupporting
confidence: 81%
“…Further, in case of oesophageal carcinoma, the importance of home nutrition is gradually gaining attention, especially in patients undergoing surgery. Several studies have shown that reasonable home nutrition therapy can improve the nutritional status, quality of life and effects of anti-tumour treatment in the patients (19)(20)(21)(22). Moreover, our study indirectly establishes the importance of home nutrition in patients with oesophageal carcinoma undergoing CCRT with an unexpected finding.…”
Section: Discussionsupporting
confidence: 66%
“…Our study results showed ONS intervention did not improve circulating concentrations of nutritional status biomarkers although hemoglobin concentration was slightly increased only in the intervention group. A recent study showed that nasopharyngeal cancer patients receiving chemoradiotherapy had higher white blood cell counts when the patients were treated with home enteral nutrition [25]. The hemoglobin concentration was negatively associated with PG-SGA score in colorectal cancer patients [26] and nutrition intervention improved the compliance rate of chemotherapy and nutritional status measured by blood concentrations of hemoglobin and albumin [27].…”
Section: Discussionmentioning
confidence: 99%